ANALISIS MODEL STANDAR TENTANG SISTEM PENDIDIKAN NASIONAL DALAM ASPEK SARANA PRASARANA DIJEJANG SEKOLAH MENENGAH PERTAMA DI KOTA SEMARANG - Teti Rosiana Hidayat; Fathurrohman Fathurrohman (Journal of Public Policy and Management Review, 2016)
Education until this time is very important to the community particularly in the city of Semarang. Mainly on the Infrastructure that makes the competing schools viewed from the Infrastructure of each school especially the achievements obtained by the schools. In education national standards of quality (quality) is education which is capable of reaching national and international quality standards and international education should have a high competitiveness in terms of education results (outputs and outcomes), the process and the input of the school both nationally and internationally. Legislation of the national education system (SISDIKNAS) No. 20 of 2003 article 45 regional rules explained above the Semarang city no. 1 in 2007 About the Organization of Education in the city of Semarang a System Infrastructure, namely article 52 The purpose of this research was to evaluate the achievement of the objectives of the National Education Policy In Semarang city Infrastructure as well as to know the implementation of the policy. This research uses descriptive qualitative approach type. Data collection techniques are used namely observation, interview, study the documentation and study of the literature. The results of this research show that the implementation of a policy of SISDIKNAS in fairly well. There is still some still lack the Infrastructure of various schools particularly in jejang middle school (JUNIOR HIGH SCHOOL) in the city of Semarang. Semarang city already reached national standards.